2017
DOI: 10.1002/jsfa.8528
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and microstructure of myofibrillar protein–olive oil composite gels: effect of different non‐meat protein as emulsifier

Abstract: Different meat or non-meat proteins as emulsifier have varied impacts on the rheology and microstructure of MP gels, indicating the potential and feasibility of these non-meat proteins as emulsifiers to modify the textural properties in comminuted meat products. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…These interactions could enhance the protein structure and retain more water. Moreover, Wu et al also observed increased WHC in heat-induced non-animal protein gels and they attributed it to a filling effect of oil droplets [ 41 ]. However, our results in Section 3.6 suggested that oil droplets are not acting as active fillers and therefore not interacting with the protein matrix, since the elastic modulus of the gels was decreasing with increasing oil content.…”
Section: Results and Discussionmentioning
confidence: 99%
“…These interactions could enhance the protein structure and retain more water. Moreover, Wu et al also observed increased WHC in heat-induced non-animal protein gels and they attributed it to a filling effect of oil droplets [ 41 ]. However, our results in Section 3.6 suggested that oil droplets are not acting as active fillers and therefore not interacting with the protein matrix, since the elastic modulus of the gels was decreasing with increasing oil content.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The protein components of MP, CPI and composite protein were investigated according to the reported method by Wu et al, with a 12% acrylamide separation gel (pH 8.8) and a 5% acrylamide stacking gel (pH 6.8) 26 . The MP‐CPI composite sols were diluted to 1 mg mL −1 and then mixed with SDS‐PAGE leading buffer (containing SDS, β ‐mercaptoethanol, bromophenol blue and glycerol) at a ratio of 1:1.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, confocal laser scanning microscopy observations proved that zein hydrolysate could absorb to the lipid droplet surfaces and form a protective coating, helping prevent the droplets from aggregating and subsequently enhancing the oxidative stability of the MP emulsion. Likewise, various non‐meat protein additives including SPI, sodium caseinate, and egg‐white protein isolate were added into heat‐induced pork MP‐olive oil composite gels as surfactants to investigate the change in the rheological properties and microstructure of the composite gels (Wu, Fei, Zhuang, Lei, & Wang, 2017). The authors opined that adding olive oil pre‐emulsified by sodium caseinate and egg‐white protein could enhance the gel strength and improve the dynamic rheological properties of MP composite during its transformation from sol to gel.…”
Section: Modification Of Mpmentioning
confidence: 99%